KEMAMPUAN TAWAS DAN SERBUK BIJI ASAM JAWA (Tamarindusindica) UNTUK MENURUNKAN KADAR COD (Chemical Oxygen Demand) PADA LIMBAH CAIR LAUNDRY - Galuh Candra Dewi; Tri Joko; Yusniar Hanani Darundiati (Jurnal Kesehatan Masyarakat (Undip), 2017)
Laundry wastewater contains varying levels of suspended solids, salts, nutrients, organic matter and pathogens that arise from clothes, detergent and fabric softener.The content of organic matter (COD) caused decline amount ofoxygenin the waterand affected toaquaticbiota. One of waste water treatment that can be done is by coagulation flocculation. The purpose of this research was to know the ability of coagulant alum and tamarind seeds powder with a variety of doses to reduce levels of COD. This experiment was true experimental research by pretest posttest with control group design. Total sample as much as 36 samples i.e. 30 sample treatment and 6 control.The result of Two Way Anova test with a significant p-value < 0.05 indicated that variation dose (p = 0,036) gave the difference in levels of COD while the type of coagulant (p = 0,669) had no differencelevels ofCOD.The average of COD levelsbeforetreatmentwas292,95mg/l,529,18 mg/l and 460,52mg/l. The optimum dose coagulant on alum and tamarind seeds powder was 2.5 grams, respectively the levels of COD became 193,0 mg/l and 188,72 mg/l. Meanwhile, the average percentage of COD level reduction with the addition alum was 55,05% while tamarind seed powder was 54,21%. The ability of alum and tamarind seed powder was not effective yet to reduce COD levels because the result were still above the standard quality based on Perda Provinsi Jawa Tengah No. 5 Tahun 2012. Therefore, need advance treatment to handle waste water.Keywords: Laundry, Chemical Oxygen Demand (COD), Alum, Tamarind Seed Powder